Public and Private Sector Environmental Reporting: Mandatory or Voluntary Regulation? - Ribeiro, Verónica Paula Lima; Monteiro, Sónia Maria da Silva (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2015)
The organisation's interest in producing an image of commitment towards the environment has motivated the development of new informational needs by the different stakeholders. Their satisfaction requires that the organization's traditional information systems change. This happens in both public and private organizations, in order to generate environmental information, not only for management purposes, but also for external disclosure. In this sense, the contents and display of the information produced by these systems must also adapt, receiving new information besides the traditional one [for example, the annual reports], including the ad hoc information, environmental report and/or sustainability report. The literature highlights that there is no consensual opinion among researchers about mandatory or voluntary reporting. In the private sector, the accounting regulations of environmental issues, specifically in what concerns the environmental information disclosure in the annual reports, presents a certain degree of development, with several initiatives, both national and international, concerning the approval of an environmental accounting standard. Nevertheless, in the public sector, the delay of specific accounting standards concerning environmental information has led public entities not to submit suitable information about their environmental management. The aim of this paper is to present the state of the art, both in public and private sector contexts, according to national and international legislation, in the annual reports or separately. A further objective, in addition, is to present a short reflection on the subject of mandatory and voluntary environmental disclosure.